Réponses

2014-02-12T22:29:54+01:00
Bonsoir,

 X^2-3+2(X^2+ 2\sqrt{3}X +3)=0\\\\ X^2-3+2X^2+ 4\sqrt{3}X +6=0\\\\ 3X^2+ 4\sqrt{3}X +3=0\\\\\Delta=(4\sqrt{3})^2-4\times3\times3=16\times3-36=48-36=12\\\\X_1=\dfrac{-4\sqrt{3}-\sqrt{12}}{6}=\dfrac{-4\sqrt{3}-\sqrt{4\times3}}{6}=\dfrac{-4\sqrt{3}-2\sqrt{3}}{6}\\=\dfrac{-6\sqrt{3}}{6}=-\sqrt{3}\\\\X_2=\dfrac{-4\sqrt{3}+\sqrt{12}}{6}=\dfrac{-4\sqrt{3}+\sqrt{4\times3}}{6}=\dfrac{-4\sqrt{3}+2\sqrt{3}}{6}\\=\dfrac{-2\sqrt{3}}{6}=-\dfrac{\sqrt{3}}{3}

Donc,

X_1=-\sqrt{3}\\\\X_2=-\dfrac{\sqrt{3}}{3}
Merciiiiiiiii Beaucoup pour ton aide !
Avec plaisir :)